Susceptibility of Plodia interpunctella (Hbn.) and Lasioderma serricorne (F.) to nitrogen protective pressurized atmosphere (Bollettino di zoologia agraria e bachicoltura, 2024)
Susceptibility of P. interpunctella and L. serricorne in airtight packagecontaining coffee has been evaluated in presence of protective atmosphere withpressurized nitrogen and carbon dioxide (0.2-0.4 bar).In each jar, previously filled with coffee (250 g) 2 cylindrical containers (0 3.7cm; h 5.5 cm) in plastic rigid transparent material were placed centrally, closedby a lid in soft plastic, with a rectangular opening, protected by a wire net topermit the content to be aired; in each container containing artificial substrate andcoffee individuals of the same stage and species were placed.On the whole P. interpunctella individuals show a longer survival on artificialdiet. II-III and IV instar larvae of P. interpunctella are the least sensitive stage,as 6 days are required to obtain 100% mortality.L. serricorne resulted to be very susceptible to nitrogen and carbon dioxide atmosphere;100% mortality occurs after 24 hours from the packaging for both diets.Eggs are the most resistant stage as no egg hatching is observed after a stay of 7and 8 days in nitrogen atmosphere respectively on coffee and artificial diet.
Keywords: Plodia interpunctella; Lasioderma serricorne; nitrogen; carbon dioxide protective pressurized atmosphere